Fever and respiratory symptoms after welding on painted steel. - Sjogren, B.; Backstrom, I.; Fryk, G.; Jakobsson, R.; Milerad, E.; Plato, Nils; Tornling, G. (Scandinavian Journal of Work, Environment & Health, 1991)
Electric-arc welding generates particles and gases that can induce chronic bronchitis and airway obstruction. In this case report two welders are described who had fever, spirometric deterioration, and bronchial hyperreactivity after welding steel painted with chloro-containing polymer lacquer. Pyrolysis of this paint releases many different compounds, for example, hydrogen chloride and complex chlorinated compounds.